2015
DOI: 10.18805/ijar.5571
|View full text |Cite
|
Sign up to set email alerts
|

Blood clotting response test for detecting resistance to second generation anticoagulant bromadiolone in house rat (Rattus rattus)

Abstract: Blood clotting response (BCR) test is a faster method with fewer ethical constraints than feed-testing and is widely used to monitor resistance. The second-generation anticoagulant, bromadiolone is being used to control rodents all over India for the last several years. To investigate whether its use has resulted in development of resistance in house rat, Rattus rattus, BCR test was standardized. Plasma samples of 15 rats of both the sexes were pooled separately and diluted with phosphatebuffered saline (pH 7.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…The use of the first generation active ingredients (warfarin, chlorophacinone & coumatetralyl) and bromadiolone was uneffective. Garg et al (2015) reported that the second generation anticoagulant, bromadiolone controled rodents all over India for the last several years. Conclusion Rattus norvegicus and Rattus rattus in Greater Cairo were still susceptible to the anticoagulant rodenticides, coumatetralyl 0.0375% and bromadiolone 0.005% by bioassay technique under laboratory conditions.…”
Section: Discussionmentioning
confidence: 99%
“…The use of the first generation active ingredients (warfarin, chlorophacinone & coumatetralyl) and bromadiolone was uneffective. Garg et al (2015) reported that the second generation anticoagulant, bromadiolone controled rodents all over India for the last several years. Conclusion Rattus norvegicus and Rattus rattus in Greater Cairo were still susceptible to the anticoagulant rodenticides, coumatetralyl 0.0375% and bromadiolone 0.005% by bioassay technique under laboratory conditions.…”
Section: Discussionmentioning
confidence: 99%
“…The INR in this context is derived by calculating the ratio of the post-treatment clotting time to the pre-treatment clotting time, which is then multiplied by the International Sensitivity Index (ISI). A ship rat is considered to be a responder (susceptible) to a given dose of anticoagulant when it has an INR ≥ 3.6 (3.5-3.8) (Garg and Singla 2015). Every reagent or equipment manufactured to calculate blood-clotting time or prothrombin time is assigned an ISI value.…”
Section: Experimental Designmentioning
confidence: 99%
“…Linear regressions for the relationship between brodifacoum dose (mg/kg of bodyweight) and proportionate increase in bloodclotting time (INR) for male (blue) and female (pink) ship rats from Akatarawa forest. The dotted line shows the INR level at which a ship rat is considered to be a responder(Garg and Singla 2015). The bars on the data points indicate standard errors, which reflect uncertainty in INR values when only the maximum pre-dose bloodclotting time could be measured.…”
mentioning
confidence: 99%
“…Determination of prothrombin time (PT), active partial thromboplastin time (APTT), and fibrinogen (FIB) and antithrombin III levels is required in the coagulation profile Kennerman and Kaya (2005). PT, is a test that commonly used to indicate of drugs for measuring the extrinsic blood coagulation system Gargy and Singla (2015). Determination of the duration of buccal mucosal bleeding, although applied at the clinical level, is not considered as an important indicator in diagnosing bleeding disorders.…”
Section: Introductionmentioning
confidence: 99%